Pengaruh Workplace Bullying dan Job Stress terhadap Turnover Intention yang Dimediasi oleh Burnout pada Karyawan Perusahaan Konstruksi di Jakarta Barat - Ramdhan, Muhammad Rangga Mardhika; Emilisa, Netania; Wijaya, Sanjuan Erlin; Fubian, Dhafa Akbar (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the influence of Workplace Bullying and Job Stress on Turnover Intention, mediated by Burnout, among employees of construction companies in West Jakarta. Based on descriptive statistical analysis, it was found that employees experience Workplace Bullying, Job Stress, and Burnout, all of which contribute to their intention to leave the company (Turnover Intention). Hypothesis testing results indicate a positive and significant influence of Workplace Bullying on Burnout and Turnover Intention, as well as Job Stress on Burnout and Turnover Intention. Additionally, Burnout has a positive and significant influence on Turnover Intention. Mediation by Burnout is also significant in the relationship between Workplace Bullying and Turnover Intention, as well as between Job Stress and Turnover Intention. These findings highlight the importance of managing the work environment to reduce bullying and stress to prevent burnout and decrease employee turnover intention. Keywords: Burnout, Construction Company Employees, Turnover Intention, West Jakarta, Workplace Bullying and Job Stress.